High temperature experiments in chemistry and materials science - Motzfeldt, K. (Chichester, West Sussex, United Kingdom : Wiley., 2013)
"The present text is centred around some central topics within high-temperature chemistry. It concerns the control and measurement of the basic properties"--
3.3.5 Insulating Materials and Installation3.3.6 MIMS Thermocouples; 3.3.7 Thermocouples for Very High Temperatures; 3.3.8 The Cold Junction; 3.3.9 Extension and Compensating Wires; 3.3.10 Control and Calibration; 3.3.11 The Measurement of Small e.m.f.'s; 3.3.12 More about Thermoelectricity; 3.4 Literature; References; 4 Radiation Pyrometry; Preamble; 4.1 Basic Principles; 4.1.1 The Nature of Heat and Radiation; 4.1.2 Formation and Propagation; 4.1.3 The Concept of the Black Body; 4.1.4 Emission, Absorbtion and Kirchhoff's Law; 4.1.5 Total Radiation, Stefan and Boltzmann.
Machine generated contents note: Foreword vii Preface ix 1 Introduction to High-Temperature Research 1 2 Basic Design of Laboratory Furnaces 11 3 Temperature Measurements 55 4 Radiation Pyrometry 93 5 Refractory Materials in the Laboratory 129 6 Vacuum in Theory and Practice 177 7 High-Temperature Furnaces and Thermobalances 229 8 The Summing Up 267 Author Index 317 Subject Index 000 .
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: High temperature chemistry -- Experiments; Materials at high temperatures -- Experiments; SCIENCE / Chemistry / Physical & Theoretical; SCIENCE -- Chemistry -- Physical & Theoretical; Science; Electronic books; Electronic books